Tourism geographies and the place of authenticity - Rickly, Jillian M. (Taylor & Francis, 2018)
Along with the earliest theories of tourism arose an interest in understanding the role of authenticity. These burgeoning efforts were based in history, anthropology, and sociology (see Boorstin, 1961; MacCannell, 1973, 1976; Cohen, 1979); yet, the subsequent infusion of geographical perspectives that spatialize authenticity have greatly enriched our conceptualizations. Indeed, these scholars were invaluable in laying the foundations of key aspects of authenticity – Boorstin (1961) in asserting tourism is comprised of pseudo-events drew attention to staged aspects of tourism encounters, MacCannell (1973; 1976) explicated the mechanisms through which staging occurs and initiated a discussion of the socio-cultural significance of authenticity, which Cohen (1979) then refined by elaborating on the various ways authenticity comes into play in tourists’ motivation for recreational, diversionary, experiential, experimental, and existential experiences. However, what these contributions were lacking was attention to the geographical, that tourism is simultaneously a mobilities and a placed-based phenomenon, and as such the roles of scale, mobilities, space, place, and landscape are crucial to experiences of authenticity.